To the public. City of New-York, ss. : Personally appeared before me, Benjamin Blagge, Esq ; one of His Majesty's justices of the peace for the city and county of New-York, Thomas Mesnard . - Blagge, Benjamin (LLMC-digital (Series), 1774)
Affidavit concerning the importation of arms from England.